Chimeric Antigen Receptor, Teamwork, Education, Assessment, and Management (CAR-TEAM): A Simulation-Based Inter-professional Education (IPE) Intervention for Management of CAR Toxicities - Harden, Avis; Ragoonanan, Dristhi; Anildes-Gubman, Daryl; McCall, David; Faltus, Kathleen; Featherston, Sarah; Shoberu, Basirat; Moffet, Jerelyn R.; Petropoulos, Demetrios; Khazal, Sajad J.; Razvi, Shehla; Mahadeo, Kris M.; et al. (Frontiers in Oncology, 2020)
Chimeric antigen receptor (CAR) therapies such as tisagenlecleucel, indicated for children and young adults with relapsed and/or refractory CD19+ acute lymphoblastic leukemia (ALL), have been associated with striking treatment outcomes and overall survival. Yet, they are also associated with unique and potentially life-threatening complications. Cytokine release syndrome (CRS) and immune effector cell-associated neurotoxicity (ICANS) are generally reversible complications of CAR therapies, but many patients may require critical care support especially if they are not promptly recognized and appropriately managed by frontline healthcare staff. As CAR therapies become more widely available, it is important that inter-professional staff members be aware of general principles regarding diagnosis and management. We hypothesized that an inter-professional education (IPE) simulation-based education intervention (CAR-TEAM) would improve knowledge base and confidence regarding complications of CAR therapies among inter-professional staff. Here, we demonstrate that following CAR-TEAM training, >90% of participants demonstrated knowledge proficiency and confidence in the IPE content area. CAR-TEAM training may serve as an important tool to establish initial and continued competency among sites introducing CAR therapies.